EVOLUSI PENGELOLAAN KAWASAN PERBATASAN INDONESIA DI KALIMANTAN UTARA - Muhammad Nizar Hidayat (Magister Administrasi Publik FISIP Universitas Mulawarman, 2017)
This research aims to describe Indonesian border management in North Kalimantan Province, this include the previous border policies when the area was still included in East Kalimantan Province. Descriptions of previous policies to contemporary policies is meant to provide some kind of guidelines for stakeholders to formulate a better policy in the future. That means, among some descriptions there will be some analitical views regarding the policies.